First, we find the slope:
\(\displaystyle{m}=\frac{{{y}{2}-{y}{1}}}{{{x}{2}-{x}{1}}}=\frac{{-{8}-{1}}}{{{5}-{2}}}=-\frac{{9}}{{3}}=-{3}\)

Use the slope-intercept form of a line and substitute the slope and a point, say (2,1) to find b: y=mx+b

1=-3(2)+b

1=-6+b

7=b

So, the equation of the linear function is y=-3x+7

Use the slope-intercept form of a line and substitute the slope and a point, say (2,1) to find b: y=mx+b

1=-3(2)+b

1=-6+b

7=b

So, the equation of the linear function is y=-3x+7